Recognizing Poland syndrome at birth: Chest wall and hand manifestations - Laysa Kasminata; Jojor Sihotang (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Poland syndrome is a rare congenital anomaly defined by unilateral agenesis or hypoplasia of the sternocostal head of the pectoralis major, with possible involvement of the pectoralis minor and variable ipsilateral chest wall and upper-limb abnormalities, including syndactyly. The presentation is typically unilateral, more often affecting the right hemithorax, while bilateral involvement is uncommon. Purpose: To report a neonatal case of Poland syndrome and describe the clinical manifestations and early management to support timely intervention and appropriate care planning. Method: A case study was conducted at Dumai Hospital involving a preterm neonate delivered to a 27-year-old woman (G2P1A0) at 27 weeks of gestation who presented with uterine contractions and stable vital signs. Prenatal ultrasonography was performed prior to delivery. After birth, the neonate underwent a structured physical examination focusing on the chest wall and upper extremities to identify congenital anomalies, followed by initial stabilization and referral based on clinical findings. Results: The patient was a female preterm neonate with findings consistent with Poland syndrome, including unilateral absence of the pectoralis major and pectoralis minor on the affected side and ipsilateral hand syndactyly. The infant was referred to the perinatology unit for ongoing monitoring and multidisciplinary management, while the mother received routine postpartum care according to hospital protocol. Conclusion: Poland syndrome may be recognizable at birth through unilateral thoracic muscle absence with ipsilateral limb anomalies, requiring careful newborn examination and early coordinated care.